2021
DOI: 10.1556/030.2021.01490
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid resistance among multidrug-resistant Mycobacterium tuberculosis clinical isolates in Iran

Abstract: The management of multidrug-resistant (MDR) and extensively drug-resistant tuberculosis (XDR-TB) presents a main challenge and the drug options for treating these infections are very limited. Linezolid (LNZ) has recently been approved for the treatment of MDR and XDR-TB. But, there are narrow data on genotypic and phenotypic LNZ resistance in clinical isolates. So, we aimed to determine the prevalence of LNZ resistance and to identify the mutations associated with LNZ resistance among clinical MDR-TB isolates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…tuberculosis , it should estimate the AUC/MIC based on the local drug resistance profile of M . tuberculosis ( 87 91 ).…”
Section: Expert Panel Recommendationsmentioning
confidence: 99%
“…tuberculosis , it should estimate the AUC/MIC based on the local drug resistance profile of M . tuberculosis ( 87 91 ).…”
Section: Expert Panel Recommendationsmentioning
confidence: 99%
“…The mutation C154R in RplC is one of the most prevalent ones (Ushtanit et al, 2021). Nevertheless, other mutations reported to LZD were summarized by Kadura et al (2020) and Khosravi et al (2021). The other prevalent mutations include G2270T, G2299, G2746A, G2814T and C2848A for Rrl.…”
Section: Resistance To Other Drugsmentioning
confidence: 99%
“…These authors also identified 2 polymorphisms in LZD resistance strains for rplC, V141I and I150N. However, they have not been completely validated to be the unique reason for LZD resistance (Kadura et al, 2020;Khosravi et al, 2021).…”
Section: Resistance To Other Drugsmentioning
confidence: 99%